Design of Vibration Energy Harvester using Piezoelectric Sensor - rahimi, ariff nazmi; Sofian Mohd; Qamarul Ezani Kamarudin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project explores the development of a vibration-based energy harvester utilizing piezoelectric sensors to convert mechanical energy into electrical energy for powering low-energy devices such as LED lighting. The primary aim is to design and evaluate a sustainable, compact system capable of capturing energy from environmental vibrations—simulated through a vibration motor—and storing it efficiently. The methodology involved integrating piezoelectric sensors with electronic components including Arduino UNO, LM7812 voltage regulator, bridge rectifier, relay module, and a 12V battery. Circuit design and prototyping were conducted using Arduino IDE, Fritzing, and SketchUp. The system was tested at various motor speeds (1000–6000 RPM), revealing a direct correlation between vibration intensity and electrical output. An array of eight piezoelectric sensors connected in parallel generated voltages up to 6V and currents up to 320 µA at peak conditions, successfully reaching the threshold to trigger energy storage and lighting. Results demonstrated improved charging rates and system efficiency with increased motor speeds and sensor counts. The project concludes that piezoelectric-based energy harvesting systems, when carefully designed and safeguarded, offer promising solutions for smart, low-power urban applications. The findings support further development toward scalable, environmentally friendly energy sources integrated within public infrastructure.